Sexuality and sexual dysfunction among women with breast cancer: a qualitative study in Kelantan, Malaysia - Ya, Siti Nuryati Che (2020)
Women’s sexuality becomes complex after breast cancer treatment and sexual health often being neglected in medical care. Sexual dysfunction is highly prevalent among women with breast cancer in Malaysia however it remains invisible in clinical management of the illness. To explore the consequences and coping strategies on sexuality and sexual health among the women with breast cancer in Malaysia. This qualitative study was conducted within phenomenological framework. 14 married women with breast cancer that fulfill the criteria for female sexual dysfunction (FSD) from Hospital USM and Hospital Raja Perempuan Zainab 2 in Kelantan participated in in-depth and photo elicitation interviews between June 2018 until December 2018. The interviews were audio-recorded, transcribed verbatim and transferred to analytic computer software NVivo® for data management. The transcriptions were analysed using thematic analysis based on the sexual script theory and meaning making theory. Finding shows that breast cancer treatments had disturbed the women’s sexual response cycle leading to changes in direction of meaning of sexuality from marriage intimacy to obligation that preferred physical affection rather than penetrative intercourse. The women struggled with feeling deficiency in gendered role. A few even noticed changes in husband’s sexual performance and these were in battling with inadequacy sentiment as a wife. Fear and guilt surfaced within the journey accompanied by the spouse’s emotion of either exposing frustration or becoming more attentive towards the women. To overcome sexual problem and sexual dysfunction, the women strived to accept the illness using religious belief and conform by altering sexual practises. These individuals positively look for solution by seeking formal healthcare advice, modify their physical appearance, active discussion with the husband and support from other survivors. A few of them passively struggle with the subject by averting the intimacy and receptive towards polygamy. The strength of this study includes phenomenological framework using in-depth and photo-elicitation interviews helps to explore delicate and sensitive issue about sexuality thoroughly. The limitations are only Malays, heterosexually married from low to middle socioeconomic background using purposive sampling were enrolled causing the finding cannot be generalised to other population. This study highlights the burden of breast cancer and its treatment on the sexual well-being of the patient and spouse hence recognising and addressing the sexual health will improve the overall survivorship experience. Women with breast cancer in this country embraced various mechanism that emphasised the pivotal role of religious belief and relationship context as key factors in the coping strategies.